Saxophone Works of the Early-Mid 20th Century - Rochelle, Elijah Mason (East Carolina University, 2023)
For my Signature Honors Project I have studied four works for classical saxophone and performed three of them. I have played saxophone for ten years as well as a variety of other instruments. I have developed a complicated relationship with the instrument, often switching quickly from love to frustration and back again throughout the years. One thing that I have learned to appreciate about the saxophone is its versatility and its ability to create such an array of characters. Saxophones have been around for less than two hundred years and at the beginning of that history, they were barely used. Even with the relatively short history of the instrument, saxophones are seen in classical music, jazz music, blues, parades, soul, funk, and almost any other genre you can think of. My signature honors project studied and showcased just one section of one genre of the saxophone’s history, only twenty-five years of classical saxophone.
Keywords: saxophone, music history, music performance